Lymphoepithelioma-like carcinoma of the renal pelvis: Pathological and therapeutic implications - Modi, Hemel (Canadian Medical Association, 2013)
A 75-year-old woman presented with a presumed urothelial carcinoma of the right renal pelvis. A radical nephroureterectomy was carried out and histological analysis of the specimen revealed lymphoepithelioma-like carcinoma. This is the seventh reported case of this normally nasopharyngeal tumour found in the renal pelvis. These tumours have a distinct histological appearance comprising sheets of undifferentiated syncytial cells on a background of lymphoid stroma. We review the pathological features of lymphoepithelioma-like carcinoma and make arguments for managing these tumours in a similar way to urothelial carcinoma.